2000
DOI: 10.1007/bf03173164
|View full text |Cite
|
Sign up to set email alerts
|

Dissonant study orchestrations of high-achieving university students

Abstract: This study focuses on the dissonant study orchestrations of highachieving university students. Advanced psychology students' dissonant study orchestrations were compared with previous findings of advanced medical students orchestrations. Further, the relation of study orchestrations to study success was examined. The subjects were 28 advanced psychology students at the University of Helsinki, Department of Psychology who returned a task booklet of learning; of these, 24 students completed a questionnaire conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 17 publications
3
50
0
1
Order By: Relevance
“…For example, Lonka and Lindblom-Ylänne (1996) compared Finnish psychology students and medical students and found that application directed learning was more typical of medical students. Subsequently, Lindblom-Ylänne and Lonka (2000) showed that application directedness is an important dimension among advanced students. Similarly, Vermunt and Vermetten (2004) concluded that application directed learning emerges relatively late as a distinct learning dimension in university students' development as a learner.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, Lonka and Lindblom-Ylänne (1996) compared Finnish psychology students and medical students and found that application directed learning was more typical of medical students. Subsequently, Lindblom-Ylänne and Lonka (2000) showed that application directedness is an important dimension among advanced students. Similarly, Vermunt and Vermetten (2004) concluded that application directed learning emerges relatively late as a distinct learning dimension in university students' development as a learner.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similarly, Biggs (1999) and Karns (2005) suggest that changes in teaching approaches are necessary to encourage students to engage in and be interested in the task itself, and to search for inherent meaning within the task. In support of this, some studies have found that students will adapt their approaches to learning to their perception of what different units demand (Eley, 1992;Lindblom-Ylanne & Lonka, 2000). Meyer (1991) defines this as "study orchestration".…”
Section: Research Cyclementioning
confidence: 99%
“…They seemed to aim for a deep understanding but due to the vast amount of information they had to learn they gave up this ambition. Other researchers have reported a similar dissonance between students' intentions and their actual approach to learning (Meyer 2000;Lindblom-Ylänne and Lonka 2000). However, some students achieved a deep understanding, despite how the subject was represented in the course.…”
Section: Influence Of the Learning Environmentmentioning
confidence: 65%